In vitro characterization of MOD‐5014, a novel long‐acting carboxy‐terminal peptide (CTP)‐modified activated FVII. Issue 3 (14th March 2018) - Bar‐Ilan, A.; Livnat, T.; Hoffmann, M.; Binder, L.; Zakar, M.; Guy, R.; Felikman, Y.; Moschcovich, L.; Shenkman, B.; Monroe, D.; Hershkovitz, O.; Kenet, G.; et al.
Abstract : Introduction: Recombinant FVIIa (rFVIIa) is an effective treatment for haemophilia through frequent administration. However, the short half‐life of rFVIIa decreases its prophylactic ability to reduce bleeding. Carboxy‐terminal peptide (CTP)‐modified FVIIa (MOD‐5014) is a long‐acting rFVIIa developed for on‐demand treatment of haemophilia using either an intravenous or subcutaneous injection with the aim of less frequent administrations, as well as for prophylactic use. Aim: The comprehensive evaluation of the activity MOD‐5014 vs commercially available rhFVIIa, as well as their interaction with cofactors and inhibitors. Methods: The in vitro characterization included clotting activity, affinity by surface plasmon resonance, cleavage of synthetic substrates, thrombin generation (TG) and rotation thromboelastometry. Results: Reduced specific activity was obtained for MOD‐5014 compared to rhFVIIa, while both compounds demonstrated comparable affinity to tissue factor (TF). MOD‐5014 showed reduced TG when spiked at a similar concentration as rhFVIIa, suggesting that an increased concentration might be needed in a clinical setting to provide initial haemostatic effect. MOD‐5014 demonstrated a slightly lower affinity for binding to activated platelets and slightly lower proteolytic activity on the platelet surface, possibly as the fusion of CTP has the potential to sterically hinder binding to both the platelet membrane and to protein substrates. Both compounds showed a similar dose‐dependent stimulatory effect on clot formation, and both showed a similar deactivation pattern following incubation with TF pathway inhibitor (TFPI), antithrombin and heparin. Conclusion: The comparable in vitro activity of MOD‐5014 and rhFVIIa paves the way for in vivo pharmacology evaluations of MOD‐5014 in preparation for clinical studies.